ANALISIS HASIL BELAJAR SISWA DITINJAU DARI KEMAMPUAN MATEMATIKA PADA MATERI TERMOKIMIA DI KELAS XI MIPA MAN 1 PONTIANAK - Nur Achmad; Tuti Kurniati; Rizmahardian Azhari Kurniawan (Universitas Muhammadiyah Pontianak, 2017)
ABSTRACT Chemistry is a part of Natural Sciences, which include understanding the concept and chemical calculation. Two concepts that should be owned by the students in understanding the chemistry to make students easy to master chemistryThe purpose of this study was to determine the student’s mathematic skills of students MIPA 11 grade MAN 1 Pontianak and to determine student’s learning outcomes in terms of mathematic skills in thermochemistry subject. The research method was descriptive. Data were collected using interview techniques and measuring. The analysis showed that average student’s mathematic skill was 82.86 whitch measured at 9 mathematical skills indicators contained in thermochemistry subject. Average student’s learning outcomes in thermochemistry subject was 44.08. Analysis of student’s answer sheets showed that students already had excellent mathematical skills was 71.43%. The data showed that the student who had difficulties in learning thermochemistry, students had lowunderstanding on chemistry concepts. The students obtained low learning outcomes in thermochemistry due to their concept. Keywords: Learning Outcomes, Mathematical Ability, Thermochemistry